Advanced exponential sliding mode control for microgrid at autonomous and grid-connected modes - A. Elnady; Mohammad AlShabi (Institute of Advanced Engineering and Science, 2021)
This paper introduces a novel control scheme for the operation of multilevel inverters forming a microgrid. The core of the suggested control scheme is an advanced (power-rate) exponential sliding mode controller. This developed controller is robust toward any variation of the system’s parameters and loads in addition to its fast and accurate performance. The presented control scheme provides advantageous characteristics to the microgrid operation in an autonomous mode (microgrid mode) and grid-connected mode. In the microgrid mode, the voltages and frequency are stable at any variable balanced and unbalanced load. In the grid-connected mode, an effective procedure for connecting the microgrid to the main grid is proposed to guarantee a seamless and fast transition to the grid-connected mode. The performance of the presented control scheme along with its proposed controller is validated by comparing its results to another linear and non-linear controllers for the same microgrid loading conditions.